2001
DOI: 10.1007/s127-001-8197-0
|View full text |Cite
|
Sign up to set email alerts
|

The Finnmark Study. A prospective population study of the social support buffer hypothesis, specific stressors and mental distress

Abstract: The results provide some support for the buffer hypothesis, and indication of specificity in the interactions between stressor and social network/social support was found.Women, in general, had a larger buffering effect from their social network than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 30 publications
7
79
1
3
Order By: Relevance
“…We found through our research that social network, such as husbands, parents, brothers, children and institutes have a big role in supporting most wives in relieving the effects of pain resulting from the arrest of their husbands, and relieving stress of interference of others as well as the stress of occupation itself. These findings were in line with other studies (Ahern et al 2004;Bültmann et al 2002;Lepore et al 1991;Olstad et al 2001;Taylor et al 2004). On the contrary people who receive low levels of social support appear to be less resistant to stressor situations (Cohen and Wills 1985).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found through our research that social network, such as husbands, parents, brothers, children and institutes have a big role in supporting most wives in relieving the effects of pain resulting from the arrest of their husbands, and relieving stress of interference of others as well as the stress of occupation itself. These findings were in line with other studies (Ahern et al 2004;Bültmann et al 2002;Lepore et al 1991;Olstad et al 2001;Taylor et al 2004). On the contrary people who receive low levels of social support appear to be less resistant to stressor situations (Cohen and Wills 1985).…”
Section: Discussionsupporting
confidence: 93%
“…Other studies did investigate the influence of having husbands arrested but for criminal reasons (Arditti et al 2003;Codd 2007;Daniel and Barrett 1981;Fishman 1990;Hairston 1998;Lenora Madison 1992;Miller 2006;Pfiffner et al 2001;Robin and Lisa 2001;Travis 2005;Wildeman et al 2012). Several studies have found that the availability of social support is essential for the wellbeing of individuals in stressful situations (Agani 2001;Ahern et al 2004;Bültmann et al 2002;Cohen and Wills 1985;Olstad et al 2001;Taylor et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo brasileiro relatou que a prevalência de depressão gestacional (37,8%) foi notavelmente maior do que as nossas estimativas, mas a amostra era pequena (n=33) e a depressão foi apurada por um questionário de rastreamento de sintomas depressivos 28 . Outros estudos em países desenvolvidos, que também utilizaram escalas para rastreamento de sintomas, relataram prevalência acima de 20% [46][47][48][49][50] . É importante enfatizar que o uso de instrumento de rastreamento tende a classificar muitos indivíduos falso-positivos como portadores de transtorno mental, aumentando a prevalência destes transtornos na população em geral.…”
Section: Discussionunclassified
“…A primeira refere-se ao fato de que a ausência desse tipo de apoio afeta diretamente a saúde mental, desencadeando transtornos. Já a segunda diz respeito ao modelo de eventos estressores, transtornos mentais nos quais o apoio social funcionaria como mediador do estresse (efeito buffer) modificando o seu efeito, ou seja, o indivíduo sem apoio social teria mais predisposição aos transtornos mentais 4 . O apoio social é um construto multidimensional que envolve o conforto, carinho, a assistência e/ou informações que alguém recebe de contatos sociais, estando ainda relacionado à percepção que a pessoa tem do seu mundo social, estratégias para estabelecer vínculos e os recursos que lhe são oferecidos [5][6][7] .…”
Section: Introductionunclassified
“…Studies addressing the problem of social support tend to focus on and emphasize the positive effects of interpersonal ties, whether in their structural or functional dimension [31][32][33]. In contrast, other authors argue that close relationships can be supportive and caring but that they can also be characterized by misunderstanding, disapproval and antagonism, depending on the fit between the function of the social support type and the patient need [7,14,34].…”
Section: Research Papermentioning
confidence: 99%